The Relationship between Leadership Style and Staff Job Satisfaction at the College of Education, Addis Ababa University - Mulugeta, Fikadu (The Ethiopian Journal of Education, 2021)
This study examines the relationship between the department heads leadership styles and the academic staff job satisfaction at Addis Ababa University in the College of Education. Fifty five academic staff in the College of Education completed the Multifactor Leadership Questionnaire (MLQ) and the Mohrman-Cooke-Mohrman Job Satisfaction Scale (MCMJSS). The result indicated that department chairs in the college have shown all range of leadership styles-transformational, transactional and laissez faire leadership styles. Similarly, the staff self reported level of job satisfaction is above average. The study also indicated that there is a significant relationship between transformational and laissez-faire leadership styles of the department chairs and job satisfactions of the academic staff. On the other hand, the relationship between transactional leadership style of the department chairs and staff job satisfaction and the transformational leadership of the department chairs and the intrinsic job satisfaction of the staff is not significant. The results of this study will provide insights into the level of staff satisfaction and the leadership styles of the department chairs at College of Education. It may also indicate the need to consider other more situational variables in the study of leadership and job satisfaction.